Irrigation and Nitrogen Fertilization Alter Soil Bacterial Communities, Soil Enzyme Activities, and Nutrient Availability in Maize Crop - Muhammad, Ihsan; Yang, Li; Ahmad, Shakeel; Zeeshan, Muhammad; Farooq, Saqib; Ali, Izhar; Khan, Ahmad; Zhou, Xun Bo (Frontiers in Microbiology, 2022)
Irrigation and nitrogen (N) fertilization rates are widely used to increase crop growth and yield and promote the sustainable production of the maize crop. However, our understanding of irrigation and N fertilization in the soil microenvironment is still evolving, and further research on soil bacterial communities under maize crop with irrigation and N management in subtropical regions of China is needed. Therefore, we evaluated the responses of two irrigation levels (low and high irrigation water with 60 and 80% field capacity, respectively) and five N fertilization rates (i.e. control (N0), N200 (200 kg N ha-1), N250 (250 kg N ha-1), N300 (300 kg N ha-1), and N350 (350 kg N ha-1)on soil bacterial communities, richness, and diversity. We found that both irrigation and N fertilization significantly affected bacterial richness, diversity index, and number of sequences. Low irrigation with N300 treatment has significantly higher soil enzymes activities, soil nutrient content, and bacterial alpha and beta diversity than high irrigation. In addition, the Proteobacteria, Actinobacteriota, Chloroflexi, and Firmicutes were the dominant bacterial phyla under both irrigation regimes. The acidic phosphates, acidic invertase, β-glucosidase, catalase, cellulase, and urease were positively correlated with the Shannon index under both low and high irrigation. Therefore, low irrigation improves soil nutrient utilization by boosting soil enzyme activity, directly affecting soil bacterial communities. It was concluded that greater soil nutrients, enzyme activities with higher bacterial diversity are the main indicators of soil reactivity to low irrigation water and N300for maintaining soil fertility and soil microbial community balance.